The development of assessment instrument for the Gambyong Pareanom dance practice - Rumiwiharsih, Rumiwiharsih (FBSB UNY, 2023)
This study aims to develop an assessment instrument for the Gambyong Pareanom dance for students of the Dance Arts Education Study Program, Faculty of Languages and Arts of Yogyakarta State University, to find out the effectiveness of the Surakarta style Gambyong Pareanom dance assessment instrument. This was a research and development study with the DDD-E model by Borg Gall consisting of several development stages, including planning, design, and development, initial product trial, initial product revision, final product revision, operational product revision, and operational product trial. This research and development study involved 30 students of the Dance Arts Education Study Program, Faculty of Languages and Arts of Yogyakarta State University. The planning stage includes a needs analysis study and formulating these needs in a development plan. The planning involved several Javanese dance lecturers in Surakarta. This planning stage was carried out by determining the scope, identifying the characteristics of learning/students, determining product limitations, and making planning documents. The second stage, namely the design stage, includes making the design of the Gambyong Dance practice assessment model, which consists of aspects of assessment (attitudes, knowledge, and skills) in accordance with the learning outcomes of the Surakarta Female Dance course. The third stage, which is development, includes initial product trial, initial product revision, final product trial, and operational product trial. The effectiveness of the model was assessed based on the percentage of lecturers’ satisfaction on the Surakarta dance course, with the Gambyong Pareanom dance material based on the results of product trial. The results of the study show that the product is an assessment sheet which includes aspects of: 1) pacak, 2) pancat, 3) ulat, 4) lulut, 5) wiled, 6) luwes, 7) wirama, and 8) gendhing, all of which referred to as Hasta Sawanda. Two other aspects (wiraga and wirasa) are added, resulting in a total of ten assessment aspects. The effectiveness of the product shows that this assessment sheet is good for assessing the Gambyong Pareanom dance. Keywords: development, instrument, assessment, dance